A strategy for efficient immobilization of laccase and horseradish peroxidase on single‐walled carbon nanotubes. Issue 12 (8th May 2013) - Li, Ying; Huang, Xirong; Qu, Yinbo
Abstract: BACKGROUND: The immobilization of biomacromolecules on carbon nanotubes has attracted considerable attention. Based on the specific affinity between concanavalin A (Con A) and glycosyl, and the ability of alkyl polyglucoside to disperse single‐walled carbon nanotubes (SWNTs), a new self‐assembly immobilization strategy is developed . RESULTS: Using laccase (Lac) and horseradish peroxidase (HRP) as models, it is demonstrated that this new self‐assembly immobilization strategy has obvious advantages over the direct adsorption immobilization strategy in enzyme loadings ( 1.34‐fold (Lac) and 1.46‐fold (HRP) higher) and in the specific activity ( 5.06‐fold (Lac) and 4.77‐fold (HRP) higher). Circular dichroism (CD) spectra and fluorescence spectra also indicate that the present new indirect immobilization strategy has less impact on the enzyme conformation compared with the direct adsorption strategy. For the catalytic oxidation of dibenzothiophene (DBT), the immobilized HRP prepared using the present self‐assembly strategy was more effective than that using the direct adsorption strategy . CONCLUSION: Based on these findings, it is concluded that the present self‐assembly strategy can greatly improve the enzymatic properties of the immobilized enzymes. © 2013 Society of Chemical Industry